Early sexual debut: prevalence and risk factors among secondary school students in Ido-ekiti, Ekiti state, South-West Nigeria - Durowade, Kabir Adekunle; Babatunde, Oluwole Adeyemi; Omokanye, Lukman Omotayo; Elegbede, Olusegun Elijah; Ayodele, Lawrence Majekodunmi; Adewoye, Kayode Razaq; Adetokunbo, Stella; Olomofe, Charles O; Fawole, Adegboyega A; Adebola, Oyebola Eyitayo; Olaniyan, Temitope O (African health sciences, 2017)
Background: Early adolescent sexual activity remains a recurring problem with negative psychosocial and health outcomes. The age at sexual debut varies from place to place and among different individuals and is associated with varying factors. The aim was to determine the prevalence and risk factors of early sexual debut among secondary school students in Ido-Ekiti, South-West Nigeria. Methodology: This was a cross-sectional study. The respondents were selected using multi-stage sampling technique. Pre-tested, semi-structured, self-administered questionnaire was used to collect data. Data was analyzed using SPSS version 15. Results: More than two-thirds, 40(67.8%), had early sexual debut. The prevalence of early sexual debut was about 11%. The mean age of sexual debut was 13.10±2.82; the mean age for early sexual debutants was 11.68±1.98. The mean number of sexual partners was 2.44±1.99. Male gender, having friends who engaged in sexual activities had association with early sexual exposure (p<0.05). Alcohol intake had the strongest strength of association for early sexual debut among the students. Conclusion: The high prevalence of early sexual exposure among the students calls for urgent interventions to stem the trend. This will help to reduce the devastating negative psycho-social and health sequels.